Kimmeridgian pliosaurids (Sauropterygia, Plesiosauria) from Tlaxiaco, Oaxaca, southern Mexico - Barrientos Lara, Jair Israel (2015)
Fossil remains of two specimens of the family Pliosauridae are described in the present manuscript. These fossils are from the Kimmeridgian shallow marine strata belonging to the informally known Sabinal formation deposited in the Tlaxiaco Basin, which are exposed in Yosobé, near Tlaxiaco town, Oaxaca State, southern Mexico. The first of these specimens consists of a fragment of premaxilla with teeth, which show diagnostic characters that allow its taxonomical identification as member of the genus Liopleurodon. The second specimen is preserved by a significantly higher number of bone elements; however, this is only identified as a member of the family Pliosauridae. Despite the shortage of the pliosaurs fossil record so far recovered in Yosobé, the specimens described here significantly contribute to the knowledge of this extinct group. On the one hand, these Kimmeridgian fossils are the southernmost representatives of these reptiles discovered in North America and the first collected in deposits of the Hispanic Corridor. On the other hand, the presence of the genus Liopleurodon in this fossil locality confirms its biogeographical distribution into the western domain of the Tethys Sea, beyond Europe.